Respuesta :

The answer is x=1 and y=6. You can solve it using a graph, substitution, or elimination. 
So you are given what x and y are. All you have to do is substitute and simplify.
Since y = -3x + 3
The y value in the first equation can be substituted for -3x + 3
I.e. x = - (-3x + 3) + 5
So where you see 'y' in the first equation, put in what y actually is.
Now simplify
x = 3x - 3 + 5 [two minuses makes a positive]
x = 3x + 2
-2x = 2
so x = 2/-2 = -1

With the value of x you found, substitute it in to find y
I.e. y = -3(-1) + 3
y = 3 + 3 = 6

So x = -1 and y = 6
ACCESS MORE